«The way to the head must be opened through the heart». Enlightenment and Herzensbildung in Schiller (Studia theodisca, 2023)
The following paper discusses Schiller’s interpretation of the German concept of Bildung, which appears to be a central term in Germany’s culture, especially (but not limited to) the educational realm. As Bildung underwent massive transformations and has been re-interpreted multiple times throughout German history, this paper will start with a definitory exercise trying to organize the dynamics surrounding the term. Secondly, a two-fold historical context – firstly regarding the wider political and social dynamics of the time and secondly, a more biographical approach focusing on Schiller – will be provided. These contextualizing efforts will be succeeded by elaborations on Schiller’s concept of Herzensbildung. The paper closes with a summary of key insights and further potential endeavors.